2017
DOI: 10.1038/s41598-017-02384-x
|View full text |Cite
|
Sign up to set email alerts
|

Tea-induced improvement of endothelial function in humans: No role for epigallocatechin gallate (EGCG)

Abstract: Consumption of tea is inversely associated with cardiovascular diseases. However, the active compound(s) responsible for the protective effects of tea are unknown. Although many favorable cardiovascular effects in vitro are mediated by epigallocatechin gallate (EGCG), its contribution to the beneficial effects of tea in vivo remains unresolved. In a randomised crossover study, a single dose of 200 mg EGCG was applied in three different formulas (as green tea beverage, green tea extract (GTE), and isolated EGCG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…The participants of this study consumed black tea (containing 150 mg polyphenols) or a placebo twice a day for eight days, and the results indicated that black tea could stimulate the circulating amount of angiogenic cells and improve acute oral fat load-induced dysfunction of endothelial cells [93]. Additionally, a RCT involving 50 healthy men compared the endothelial protective effects of EGCG in three formulas including a green tea beverage, green tea extract, and pure EGCG, and found that only the green tea beverage could improve flow-mediated dilation [94]. Another RCT conducted with 14 healthy participants found that the intake of green tea polyphenol-enriched ice cream could immediately enhance vascular function and reduce oxidative stress [95].…”
Section: Clinical Trailsmentioning
confidence: 99%
“…The participants of this study consumed black tea (containing 150 mg polyphenols) or a placebo twice a day for eight days, and the results indicated that black tea could stimulate the circulating amount of angiogenic cells and improve acute oral fat load-induced dysfunction of endothelial cells [93]. Additionally, a RCT involving 50 healthy men compared the endothelial protective effects of EGCG in three formulas including a green tea beverage, green tea extract, and pure EGCG, and found that only the green tea beverage could improve flow-mediated dilation [94]. Another RCT conducted with 14 healthy participants found that the intake of green tea polyphenol-enriched ice cream could immediately enhance vascular function and reduce oxidative stress [95].…”
Section: Clinical Trailsmentioning
confidence: 99%
“…Green tea (equivalent to 200 mg EGCG/d) treatment was also observed to improve the endothelial function in humans in terms of flow-mediated dilation. However, its isolated EGCG might not contribute to this improvement [139]. Furthermore, tea consumption also reduced hyperlipidemia in humans [141,142].…”
Section: Cardiovascular-protective Effect In Humansmentioning
confidence: 98%
“…It was reported that short-term daily consumption of three capsules containing 500 mg of green tea extract could reduce blood pressure in obese prehypertensive women [135]. In addition, tea consumption also improved the endothelial function in humans, and green and black teas may be equally effective with regard to improve endothelial function [136][137][138][139][140]. Acute black tea intake (200 mL/day) for seven days enhanced the cutaneous vascular response to gradual local heating to 42 • C in healthy, middle-aged participants, which was probably induced by activating endothelium-derived chemical mediators like NO [136].…”
Section: Cardiovascular-protective Effect In Humansmentioning
confidence: 99%
“…Although tea has many anti-oxidant properties, the effects of black tea and green tea on endothelial function are also shown in Table 1 since tea contains caffeine. As shown in Table 1, the acute and chronic effects of coffee and caffeine on endothelial function were examined in healthy subjects, subjects with CV risk factors, and patients with CVD using several endothelial function tests [31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,77,78,79,80,81,82,83,84,85,86].…”
Section: Effects Of Coffee and Caffeine On Endothelial Functionmentioning
confidence: 99%
“…All of the studies using black tea or green tea showed significant augmentation of FMD in healthy subjects and significant improvement of FMD in subjects with coronary risk factors and patients with CAD, while the effects of tea on NID were controversial (Table 1) [80,81,82,83,84,85,86].…”
Section: Effects Of Coffee and Caffeine On Endothelial Functionmentioning
confidence: 99%